IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISME PADA PEMBELAJARAN FIQIH - Lailatun Nafisah; Andi Warisno; Mujiyatun; Suci Hartati (UNISAN JURNAL, 2022)
The purpose of this study is how to implement constructivism learning theory in Fiqh learning in class VII at MTs Hidayatul Mubtadiin Sidoharjo Jati Agung, South Lampung. What are the Factors Affecting the Implementation of Constructivism Learning Theory in Fiqh Learning in Class VII at MTs Hidayatul Mubtadiin Sidoharjo Jati Agung, South Lampung. This study uses a descriptive qualitative approach. Data collection techniques with observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and conclusion drawing. The result of this research is that the implementation of constructivism learning theory in Fiqh learning based on various media in grade VII at MTs Hidayatul Mubtadiin is quite good, where this theory prioritizes student independence and involvement in the learning process. And the factors that influence the implementation of the Constructivism Learning Theory are supporting factors in the form of: teacher skills and expertise, facilities and infrastructure, research locations. and the inhibiting factors are: it is difficult to change the beliefs and habits of the teacher, the creativity of the teacher, the students are accustomed to teacher-centered learning.